2020
DOI: 10.5456/wpll.22.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Situating the evidence for impact of outreach strategies: A systematic review for improving access to higher education

Abstract: Efforts to widen participation into higher education (HE) are having an impact with increasing numbers of diverse students accessing HE. Outreach is a key strategy within widening participation (WP), yet there has been little peer reviewed, published evidence regarding how outreach is identified, situated and understood. This paper addresses this gap, presenting a systematic review of published research examining how the impact of WP outreach is identified and understood in UK research. The Preferred Reportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This regional evaluation of the UC programme shows that Specifically, it addresses the lack of evidence on impact from programmes delivered in the UK (Younger et al, 2019 andHeaslip et al, 2020). It also highlights the importance of robust evaluation and the usefulness of applying the NERUPI framework in this context, in assessing the impact of transformative outreach activities on intended outcomes.…”
Section: Challengementioning
confidence: 90%
See 1 more Smart Citation
“…This regional evaluation of the UC programme shows that Specifically, it addresses the lack of evidence on impact from programmes delivered in the UK (Younger et al, 2019 andHeaslip et al, 2020). It also highlights the importance of robust evaluation and the usefulness of applying the NERUPI framework in this context, in assessing the impact of transformative outreach activities on intended outcomes.…”
Section: Challengementioning
confidence: 90%
“…In their systematic review of evidence on the effectiveness of interventions and strategies for widening participation in HE, Younger et al (2019) found just 16 studies, out of some 3,500, were relevant to the UK context and of high enough quality to be included in the final review. Likewise, Heaslip et al's (2020) recent systematic review of studies established that just 26 out of 847 were UK-focused. The review aimed to explore how current research identifies and understands impact in outreach activities over the ten-year period 2005 to 2015.…”
Section: Literature and Theoretical Frameworkmentioning
confidence: 99%